STRATEGI KUA KECAMATAN BANGUNTAPAN DALAM MENGATASI PERKAWINAN ANAK DI KAPANEWON BANGUNTAPAN KABUPATEN BANTUL DAERAH ISTIMEWA YOGYAKARTA - Arum Al Fakih; Maulana Umar Inamul Hasan; Nurulia Shalehatun Nisa (Qiyas : Jurnal Hukum Islam dan Peradilan, 2022)
Abstract: The research aimed to describe the issue of child marriage in the Banguntapan sub-district and the strategies used by the KUA (Islamic Religious Affairs Office) of the Banguntapan sub-district in addressing this issue. The research was descriptive and analytical and was conducted at the KUA of the Banguntapan sub-district. Data was collected through interviews and documentation. Primary data were obtained from interviews with the KUA of the Banguntapan sub-district, while secondary data was obtained from books, scholarly articles, laws, and other relevant documents. The research results showed an increase in child marriage in Kapanewon Banguntapan. The strategies used by the KUA of the Banguntapan sub-district to address this issue include prevention and guidance. The KUA of Banguntapan sub-district implemented prevention strategies by enforcing the minimum age for marriage as per the Marriage Law, participating in educational activities on the dangers of child marriage within the community, such as in Majelis Ta’lim and Program Keluarga Harapan, and providing pre-marriage guidance for teenagers in schools. If child marriage cannot be prevented, the KUA of the Banguntapan sub-district guides to ensure that the families from child marriage can achieve the goals of a peaceful, loving, and compassionate marriage.Keywords: child marriage, KUA strategy, maṣlaḥah mursalah